Addressing the malaise in neoclassical economics: A call for partial models - Ronald L. Wallace (Kiel Institute for the World Economy (IfW), 2017)
Economics is currently experiencing a climate of uncertainty regarding the soundness of its theoretical framework and even its status as a science. Much of the criticism is within the discipline, and emphasizes the alleged failure of the neoclassical viewpoint. This article proposes the deployment of partial modeling, utilizing Boolean networks (BNs), as an inductive discovery procedure for the development of economic theory. The method is presented in detail and then linked to the Semantic View of Theories (SVT), closely identified with Bas van Fraassen and Patrick Suppes, in which models are construed as mediators creatively negotiating between theory and reality. It is suggested that this approach may be appropriate for economics and, by implication, for any science in which there is no consensus theory, and a wide range of viewpoints compete for acceptance.
Keywords: B41; 330; Economic models; history of economic theory; complexity economics; computational modeling; Boolean networks; semantic view of theories